Principles of cross-border insolvency law / Reinhard Bork. - Bork, Reinhard (Intersentia, 2017)
The thesis of this book is that cross-border insolvency rules of all kinds (e.g. European Insolvency Regulation, UNCITRAL Model Law, ALI Principles for the NAFTA States, national laws such as Chapter 15 US Bankruptcy Code or Sch. 1 Cross-Border Insolvency Regulation 2006) are founded on, and can be traced back to, basic values and that they aim to pursue and enforce such standards. Furthermore, several principles can be identified, distinguished and sorted into three groups: conflict of laws principles (e.g. unity, universality, equality, mutual trust, cooperation and communication, subsidiarity, proportionality), procedural principles (e.g. efficiency, transparency, predictability, procedural justice, priority) and substantive principles (e.g. equal treatment of creditors, optimal realisation of the debtor's assets, debtor protection, protection of trust (for secured creditors or contractual partners), social protection (for employees or tenants)). Using the principle-oriented approach, the book will have a significant impact for both deciding cases and shaping cross-border insolvency law. It offers both legislators and courts new substantive and methodological support in making decisions, for example where the treatment of secured creditors, support for foreign insolvency practitioners or even harmonisation of cross-border insolvency laws is at stake. About the author: Prof. Dr. Reinhard Bork holds the Chair in Civil Procedural Law at the University of Hamburg. He has been the Robert S. Campbell Visiting Fellow at Magdalen College, Oxford in 2010-2011 and 2015-2016. He is an experienced Court of Appeal Judge and arbitrator. 'The present book is clearly the product of massive and admirable research ... It is a major step forward in learning on the subject.' From the Foreword by Gabriel Moss QC' Professor Bork's important book identifies and systematically articulates a set of core foundational principles for cross-border insolvency law. His principled-based approach provides the basis for evaluating existing legal frameworks, such as the European Insolvency Regulation and the UNCITRAL Model Law, and for constructing a harmonized, transnational, normative order of insolvency law. Academics, law reformers, judges, and practitioners would be well advised to pay close attention to Professor Bork's excellent, clear-sighted and scholarly insights.' Adrian J. Walters, Ralph L. Brill Professor of Law, Chicago-Kent College of Law'[This book is] very interesting as a comprehensive survey of the major substantive and procedural principles governing the cross-border insolvency phenomenon.' Antonio Leandro, Associate Professor of International Law at the University of Bari Aldo Moro